A review of recent developments in natural fibre composites and their mechanical performance - Pickering, K.L.; Efendy, M.G. Aruan; Le, T.M. (Composites. Part A, Applied science and manufacturing, 2016)
Recently, there has been a rapid growth in research and innovation in the natural fibre composite (NFC) area. Interest is warranted due to the advantages of these materials compared to others, such as synthetic fibre composites, including low environmental impact and low cost and support their potential across a wide range of applications. Much effort has gone into increasing their mechanical performance to extend the capabilities and applications of this group of materials. This review aims to provide an overview of the factors that affect the mechanical performance of NFCs and details achievements made with them.